Bilingualism matters language learning across the lifespan - Garraffa, Maria; Sorace, Antonella; Vender, Maria; Schwieter, John W. 1979- (Cambridge University Press, 2023)
What happens in the brain when learning a second language? Can speaking more than one language provide cognitive benefits over a lifetime? What implications does an increase in bilingualism have for society? And what are the factors that can promote and support bilingualism in children and adults? This book - a translated and adapted version of Il Cervello Bilingue (2020) - answers these questions and more, providing the reader with a comprehensive yet concise guide on different topics related to bilingualism. Based on the results of the most recent studies conducted internationally, it discusses recent research findings, explains terminology, and elaborates on the current state of the field, with the aim of providing families and society with suggestions about how to encourage bilingualism. Written in an engaging and accessible style, it takes both academics and readers with no prior knowledge of the field on a journey into the bilingual brain